Incomplete without the other: Isaac, Ishmael and a hermeneutic of diversity - Amos, Clare (Islam and Christian-Muslim relations, 2009)
The article begins by acknowledging the way that, in Islamic tradition (though not necessarily in the Qur'an itself), the ‘sacrificed son’ of Abraham appears to be Ishmael. This differs from the Bible, where the ‘sacrificed son’ is clearly Isaac. Yet a closer look at the Bible in fact suggests that the stories of Isaac and Ishmael in Genesis are woven together through a number of important literary connections which will be explored in some detail. This will lead to a wider consideration of the themes of universality and particularity in the Abraham cycle. The article seeks to argue that the very structure of the biblical narrative in Genesis challenges readers to move beyond a ‘particularistic’ understanding of scripture, and finally to ask whether the way that Isaac and Ishmael are ‘bound together’ has implications for Christian and Muslim use of our respective scriptures, i.e., that we are ‘incomplete without the other’ and their understanding of the story.